Involved-field radiation therapy for selected cases of recurrent ovarian cancer - Kim, Nalee (J Gynecol Oncol, 2019)
OBJECTIVES: In our institutional experience, involved-field radiation therapy (IFRT) yields favorable outcomes in patients with recurrent epithelial ovarian cancer (EOC). This retrospective study aimed to investigate the clinical benefits of IFRT in this patient population. METHODS: Among patients treated with IFRT for recurrent EOC between 2010 and 2017, 61 patients with 90 treatments were included. IFRT encompassed all treatable lesions identified via imaging studies with 10–15-mm margins. Prescribed doses were ≥45 Gy (equivalent dose in 2 Gy/fraction). RESULTS: Patients were followed up for a median of 19.0 (Interquartile range, 8.6–34.9) months after IFRT. The 2-year in-field control, progression-free survival, and overall survival (OS) rates were 42.7%, 24.2%, and 78.9%, respectively. Fifty-three IFRT sessions (58.9%) were followed by systemic chemotherapy, and the median chemotherapy-free interval (CFI) was 10.5 (95% confidence interval=7.3–13.7) months. A higher carbohydrate antigen-125 (CA-125) level correlated with a worse 2-year OS (69.2% vs. 91.0%; p=0.001) and shorter median CFI (4.7 vs. 11.9 months; p<0.001). Twenty-eight (31.1%) of 90 treatments yielded a long-term CFI >12 months. For patients with a normal CA-125 level and/or platinum-sensitive tumor, IFRT prolonged CFI regardless of pre-existing carcinomatosis, gross tumor volume, and number of treatment sites. CONCLUSION: Our early experience demonstrates the safety and feasibility of IFRT as an effective salvage therapy and enables a “chemotherapy holiday” in selected recurrent EOC settings. The CA-125 value before IFRT (within normal range) and/or platinum sensitivity could be used as selection criteria for IFRT.